Atmosfera controlada na conservação de erva-mate - Prestes, Sarah Lemos Cogo (2014)
The main aim of this work was to evaluate the effect of controlled atmosphere on postharvest conservation of yerba mate. The following aspects were evaluated: color, chlorophylls concentration, carotenoids and phenolic compounds, foaming, mold and yeast count and the bitter taste of yerba mate. Thus, three experiments were performed from samples of yerba mate from Arvorezinha (RS) and São Mateus do Sul (PR) in the form [1] thickly ground ( cancheada ) and thinly milled ( socada ) were stored in four oxygen levels (1, 3, 6 and 20.9 kPa O2) and four dioxide carbon levels (0, 3, 6 and 18 kPa CO2), and analyzed, after nine months of storage [2] native and cultivated yerba mate stored at room temperature, 1.0 kPa O2 and 3.0 kPa CO2 analyzed after 0, 3, 6 and 12 months of storage. [3] native and cultivated yerba mate from São Mateus do Sul (PR) stored in an atmosphere containing: 20.9 O2 + 0.03 CO2; 0.5 O2 + 0.03 CO2; 1.0 O2 + 0.03 CO2; 1.0 O2 + 3.0 CO2; 1.0 O2 + 18 CO2 which were analyzed after six months of storage. The results demonstrate that the condition 1.0 kPa O2 maintain the yerba mate greener and with a higher chlorophylls concentration and total phenolic compounds. The CO2 partial pressure maintain yerba mate coloration greener and with a higher chlorophylls concentrationand total phenolic compounds, regardless of the level used, in the yerba mate from both cultivation areas. The yerba mate thickly ground ( cancheada ) presented a better storage potential than the thinly milled ( socada ). Total chlorophyll concentration reduced exponentially during the storage time independently of the storage condition, form of cultivation and place that the yerba mate was cultivated, since the total carotenoid independently of the form and place of cultivation decreased to 3 months storage under atmosphere of 1.0 kPa O2. When stored in 3.0 kPa CO2, the reduction was over 12 months of storage. Dioxide carbon increasing in the storage chamber increases the phenolic compounds concentration until six month of storage. Raw material originated from São Mateus do Sul-PR has higher chlorophyll concentration, greener color resulting in greater storage potential of this yerba mate. When evaluating the combination of gases, we observed that CA condition with 0.5 kPa O2 + 0.03 kPa CO2 maintained yerba mate greener, with higher chlorophyll concentration and phenolic compounds concentrations after 6 months of storage. As for the foam, controlled atmosphere had a positive effect on its maintenance. The native yerba mate showed higher green color preservation in relation to the cultivated. There was no increase in yeast and molds in yerba mate of CA storage. Yerba mate, independently of type, stored in 1.0 kPa O2 + 0.03 kPa CO2 was selected in a sensorial panel as the most bitter and under air conditions (20.9 kPa O2 + 0.03 kPa CO2) as the lesser bitter, however, the most preferred yerba mate stored under 0.5 O2 kPa + 0.03 kPa CO2.